Effect of carvedilol on portal hypertension depends on the degree of endothelial activation and inflammatory changes - Bruha, Radan; Vitek, Libor; Petrtyl, Jaromir; Lenicek, Martin; Urbanek, Petr; Zelenka, Jaroslav; Jachymova, Marie; Svestka, Tomislav; Kalab, Milan; Dousa, Miroslav; Marecek, Zdenek (Scandinavian journal of gastroenterology, 2006)
OBJECTIVE: Bleeding from esophageal varices is a major complication of liver cirrhosis. Non-selective beta-blockers exert an influence on the functional part of portal hypertension, thereby reducing the risk of bleeding. Direct measurement of this functional part is not possible; nevertheless, pro-inflammatory markers as well as parameters of endothelial dysfunction might serve as surrogate markers. The aim of study was to assess the correlation between the therapeutic efficacy of carvedilol and markers of endothelial dysfunction and systemic inflammation in patients with liver cirrhosis and portal hypertension. MATERIAL AND METHODS: Thirty-six patients with cirrhosis and portal hypertension were given carvedilol, 25 mg q.i.d. for 30 days. Hepatic venous pressure gradient (HVPG) and biochemical determinations were performed prior to and after the treatment. Eight healthy individuals served as controls for comparison of biochemical markers. RESULTS: In the whole group of cirrhotic patients, HVPG decreased from 17.7+/-3.8 to 14.9+/-4.8 mmHg (p<0.001). Complete response was seen in 15 patients (42%). Baseline serum levels of E-selectin were significantly higher in responders than in non-responders (119.8+/-70.6 versus 52.6+/-25.7 ng/ml; p=0.023) and in controls (28.8+/-22.2 ng/ml; p=0.004). Furthermore, baseline TNF-alpha levels were significantly higher in responders than in non-responders (22.8+/-15.7 versus 7+/-8.9; p=0.047) and in controls (5.5+/-5.9 pg/ml; p=0.005). Serum levels of ICAM-1 showed the same trend (4360+/-2870 versus 2861+/-1577 versus 651+/-196 ng/ml), although differences did not reach statistical significance. CONCLUSIONS: Markers of systemic inflammation and endothelial dysfunction seem to predict the hypotensive effect of carvedilol on portal hypertension in patients with liver cirrhosis and may be useful in the assessment of the efficacy of the therapy.
Keywords: venae hepaticae; Humans; Endothelium, Vascular; lidé středního věku; Propanolamines; cévní endotel; jaterní cirhóza; Carvedilol; karvedilol; Female; propanolaminy; Inflammation; lidé; beta blokátory; Biomarkers; Liver Cirrhosis; zánět; TNF-alfa; biologické markery; ženské pohlaví; mezibuněčná adhezivní molekula-1; E-selektin; Male; Hypertension, Portal; Carbazoles; Middle Aged; Venous Pressure; venózní tlak; Tumor Necrosis Factor-alpha; portální hypertenze; Intercellular Adhesion Molecule-1; mužské pohlaví; Adrenergic beta-Antagonists; karbazoly; Hepatic Veins; E-Selectin